Long-term Study on the Statistical Properties of Uterine and Umbilical Arterial Resistance Indexes by Simple Doppler Velocimetry in Patients with Perinatal Prognosis Stratification: Part I - García González, Salvador (CIENCIA ergo-sum, 2017)
The simple Doppler velocimetry is a non-invasive morpho-functional technique with great impact as a diagnostic auxiliary means in Perinantal Medicine, and has lead to the adoption of many functional indexes. A question which remains to be answered is: what is the probable interaction between uterine and umbilical arterial resistance indexes during fetal life? The answer will explain the effect of risk factors and/or final changes induced by etiopathogenic agents. The hypothesis of the present approach is that the statistical variability of such indexes is directly related to the biological strategy to achieve cardiovascular adaptation during the perinatal lapse. Hence, the goal of this study is to analyze the statistical variability for both uterine and umbilical arterial resistance indexes, from long-term observations in three patients with very different perinatal prognoses but sharing the common final condition of a live newborn child. This report tests the adjustment for the Gaussian distribution and the lineal regression for the data of the simple Doppler velocimetry.